Influência do método de amostragem nas estimativas de detecção e ocupação de peixes elétricos (Gymnotiformes) em igarapés da Reserva Ducke, Amazônia Central - Andrade, André Luiz Ramos Holanda de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2016)
Recording species occurrence is not always a simple task, because it is subject to flaws in the detection. Fishes of the Gymnotiformes can be difficult to detect, since they have nocturnal and cryptobiotic habits. On the other hand, gymnotiforms can send electrical signals, which can be detected using electrical signal detectors. However, fish sampling rarely includes the use of such detectors, which may underestimate its abundance and diversity. This study compares probabilities of detection and habitat occupancy of Gymnotiformes in streams of Ducke Reserve, Brazilian Amazon, from samplings with and without the use of electrical detectors, and evaluates the influence of environmental variables on such probabilities. Single species, single season models were employed, with model selection based on Akaike Information Criterion. Samplings were done in 31 streams in 2005, 2006 (twice), 2011, and 2015 (twice). Electrical signal detector increased the probability of finding a gymnotiform by nearly 10 times, which may strongly affect conclusions about species richness and species composition in streams. The main factors interfering with gymnotiform detection were substrate type and current velocity. We conclude that the use of electrical signal detector is of foremost importance to generating accurate estimates of abundance of Gymnotiformes in streams.
Keywords: Peixes elétricos; Igarapés; Variáveis ambientais